Development of a switchless sorption compressor for the cryogenic refrigeration within the METIS instrument: Part II. Experimental demonstration. (October 2017) - Wu, Y.; Vermeer, C.H.; Holland, H.J.; Benthem, B.; ter Brake, H.J.M.
Highlights: A switchless sorption compressor for METIS cooler is experimentally demonstrated. Experiments show the sorption-compressor cells have well predicted performance. The radial-conductance-enhanced cells show improved performance. The effects of cycle time and heat-sink temperature on performance are investigated. The experimental result showed good agreement with the simulations. Abstract: Due to its vibration-free feature, sorption-based refrigeration technology has been proposed for the cryogenic cooling of the Mid-infrared E-ELT Imager and Spectrograph (METIS) instrument in the European Extremely Large Telescope. Sorption compressor is the most critical component in the METIS sorption refrigerator. A switchless sorption compressor has been designed for replacing the conventional gas-gap heat switch design. In this paper, the METIS switchless sorption compressor is validated in an experimental setup with a down-scaled version. The detailed design of the sorption compressor is introduced and the experimental setup is described. Then, the experimental procedures and results are discussed, including single-cell operation, multi-cell operation, and verification of the effects of the aluminum-foil inserts, the cycle time and the heat-sink temperature on the compressor performance. Finally, the experimental result showed good agreement with the simulations, and the deviation from the simulation to the measurement is caused by the model input inaccuracy.